Data Management in the Worldwide Sensor Web - Balazinska, Magdalena; Deshpande, Amol; Franklin, Michael J.; Gibbons, Phillip B.; Gray, Jim; Nath, Suman; Hansen, Mark; Liebhold, Michael; Szalay, Alexander; Tao, Vincent (IEEE Pervasive Computing, 2007)
Harvesting the benefits of a sensor-rich world presents many data management challenges. Recent advances in research and industry aim to address these challenges.